Evaluation of heat transfer through wall in Malaysia- a case study of UiTM test cell / Zaidatul Salwa Mahmud - Mahmud, Zaidatul Salwa (2010)
This is a study to evaluate the heat transfer through walls of different building orientation in the local climate. A test cell located in the campus of UiTM Shah Alam is used as case study. Data of the internal and external surface temperature for walls at the for orientations of North, South, East and West were measured using thermocouple type T. there were recorded on automated data logging system at an interval of 10 minutes for a duration of 5 days. The heat transfer for each wall orientation were calculated and compared. The building OTTV was also calculated and checked for the MS compliance. And finally the thickness of the east and west wall to minimize heat gain were calculated and proposed. The results show that the maximum heat gain through North and South walls are 159.9 W at 2.30 pm on the 1st day, and 169.25 W at 12.40 pm on the 2nd day respectively. The MS for building OTTV is 50W m"2 and for this test cell the value is 0.97W m'2. The calculated wall thicknesses of brick material are 0,228m for east wall and 0.345m for west wall.